Deoxygenation of oximes for the synthesis of pyrrolines via hydroimination cyclization. Issue 16 (5th April 2023) - Han, Wencheng; Liu, Wen-Deng; Su, Junqi; Zhao, Jiannan
Abstract : A series of pyrrolines were synthesized via cyclization of iminyl radicals, which were generated by photocatalytic deoxygenation of oximes with trivalent phosphine. Abstract : Herein, we report the generation of iminyl radicals through photocatalytic deoxygenation of oximes with trivalent phosphine. The hydroimination reaction proceeded via β-scission of a phosphoranyl radical, followed by 5- exo-trig cyclization of the resulting iminyl radical. This protocol transforms oximes, including alkyl oximes, into a variety of pyrrolines in moderate to good yields. A radical clock experiment confirmed the formation of a cyclic radical and supported our reaction design.